Differences Between the Integration of Avian Myeloblastosis Virus DNA in Leukemic Cells and of Endogenous Viral DNA in Normal Chicken Cells - Evans, R. M. (1974)
The nature of integrated viral DNA in normal and leukemic chicken cells has been studied by sequential nucleic acid hybridization procedures that localize the viral specific DNA in cellular DNA regions differing in reiteration frequency. First, DNA·DNA reassociation was employed to fractionate cellular DNA sequences according to their reiteration frequencies. Next, the DNA in each fraction was denatured, immobilized on nitrocellulose filters, and then hybridized with viral [(3)H]RNA. In normal cells, endogenous viral DNA appears to be associated with cell sequences reiterated 1200 times, and each integration unit appears to have a maximal size approximately equivalent to the 35S RNA subunit of the virion. In infected cells, additional viral sequences are found which reassociate as if they integrated adjacent to unique cellular DNA, or in tandem with endogenous viral DNA.